Identifikasi Kebutuhan Usaha Hulu dan Hilir Usaha Rumahan Permen Jahe di Sukabumi - Sularso Budilaksono; Rilla Sovitriana; Nana Trinawati; Alifatqul Maulana (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2023)
The ginger candy home business has become an attractive option for the people of Sukabumi City. However, upstream and downstream problems in this business are still not clearly identified. This service aims to identify upstream and downstream needs for ginger candy home-based businesses in Sukabumi City. The methods used are discussions and interviews with business owners and related stakeholders. The results of this service are expected to provide a better understanding of the problems faced by home-based ginger candy entrepreneurs in Sukabumi City and provide recommendations for more sustainable business development both upstream and downstream. This service provides contributions and benefits for MSME entrepreneurs in the ginger planting strategy sector in the form of beds and the potential for processed ginger, for example into biscuits, syrup, ginger serey drink, donuts, etc.